Drimia edwardsii (Asparagaceae, Scilloideae), a new urgineoid species from the Mkhomazi River Valley of eastern South Africa - Crouch, Neil R.; Martinez-Azorin, Mario (Phytotaxa, 2015)
A new species endemic to South Africa, Drimia edwardsii, is described and illustrated, with data provided on its morphology, ecology and distribution. The species appears to be closely related to Drimia delagoensis and Urginea lydenburgensis, and whereas all are synanthous and produce small, pale-brownish campanulate flowers, several leaf and bulb features clearly distinguish the new species.